THE RATES OF ASSIGNMENT OF THESAURUS TERMS IN THE ERIC INFORMATION RETRIEVAL SYSTEM: AN ANALYSIS OF HIERARCHIES AND LEVELS - HENRY, GEORGIANNA; DIODATO, VIRGIL (Journal of documentation, 1991)
The study examined the rates of use of descriptors in the ERIC system during 1966-1986 to determine if certain levels of terms were used more than others and if patterns of use were similar among hierarchies in the ERIC Thesaurus. The postings per document measure indicated how often a term had been assigned to documents during its life. This was averaged for each level in the 252 multilevel hierarchies. With little exception there was not much variation in postings per document among levels nor among hierarchies. The major exception was the mean rate of 725 postings per 100,000 documents for the broadest terms in the twenty-nine hierarchies having four levels each. This rate was significantly higher than for the narrowest levels in these hierarchies. The lack of variation in most hierarchies suggests that all terms currently in the system are important and used by indexers. Searchers should be aware of the power of the broadest terms.